A novel perspective on MOL-PCR optimization and MAGPIX analysis of in-house multiplex foodborne pathogens detection assay - Reslova, Nikol; Huvarova, Veronika; Hrdy, Jakub; Kasny, Martin; Kralik, Petr (Scientific reports, 2019)
Multiplex oligonucleotide ligation-PCR (MOL-PCR) is a rapid method for simultaneous detection of multiple molecular markers within a single reaction. MOL-PCR is increasingly employed in microbial detection assays, where its ability to facilitate identification and further characterization via simple analysis is of great benefit and significantly simplifies routine diagnostics. When adapted to microsphere suspension arrays on a MAGPIX reader, MOL-PCR has the potential to outperform standard nucleic acid-based diagnostic assays. This study represents the guideline towards in-house MOL-PCR assay optimization using the example of foodborne pathogens (bacteria and parasites) with an emphasis on the appropriate choice of crucial parameters. The optimized protocol focused on specific sequence detection utilizes the fluorescent reporter BODIPY-TMRX and self-coupled magnetic microspheres and allows for a smooth and brisk workflow which should serve as a guide for the development of MOL-PCR assays intended for pathogen detection.
Keywords: nemoci přenášené potravou; Yersinia enterocolitica; Toxoplasmosis; Yersinia Infections; Humans; infekce yersiniemi; Multiplex Polymerase Chain Reaction; Toxoplasma; toxoplazmóza; lidé; multiplexová polymerázová řetězová reakce; Foodborne Diseases